Analisis Keterampilan Mengajar Mahasiswa Pendidikan Guru Pendidikan Anak Usia Dini Pada Program Kampus Mengajar - Nila Fitria; Astri Lestari; Nurfadilah Nurfadilah (Universitas Al Azhar Indonesia, 2022)
Kampus Mengajar Program is one of Merdeka Belajar Kampus Merdeka (MBKM)'s program which gives university student one semester opportunity in helping elementary and junior high school teachers and head master to hold teaching and learning activity affected by pandemic covid 19. The campus teaching program provides opportunities for PG PAUD students to implement teaching skills as a provision to become teachers that have been obtained in college. The research method used is descriptive with a qualitative approach which aims to analyze the teaching skills possessed by PG PAUD students during the campus teaching program. The results showed that the campus teaching program became a space for PG PAUD students to implement and develop their teaching skills. Three PG PAUD students who participated in the campus teaching program (100%) were placed in grade 1, two students (66.7%) in grade 6 and one student (33.3%) in grade 4. PG PAUD students were skilled in applying various teaching skills such as questioning skills, reinforcement skills, variation skills, explaining skills, opening and closing lessons, small group guiding skills and classroom management skills. However, students need to improve their teaching skills in managing classes and guiding small group discussions. As well as the need for coordination between students and campus teaching partners (schools) regarding cooperation to apply classroom management skills.Keywords – Kampus Mengajar Program, PG PAUD Students, Teaching Skil.